Konsep Disruptive Marketing dalam Menanggulangi Praktik Jual Rugi oleh Perusahaan Penyedia Jasa Transportasi Online - Anggraini, Ayusiva; Priyo Amboro, F. Yudhi; Hotmaulana Hutauruk, Rafinus (Jurnal Supremasi, 2024)
The rapid development of app-based online transportation in Indonesia addresses the public's need for application-based transportation modes. However, intense competition among app-based transportation providers has led to the emergence of predatory pricing strategies. To investigate these practices and their implications for the relevant market and disruptive market from a legal perspective, a normative legal research was conducted. The results reveal regulatory ambiguities concerning promotional pricing concepts in online transportation companies, which have led to predatory pricing practices violating Article 20 of Law Number 5 of 1999. This discrepancy reflects legal frameworks lagging behind technological advancements, contrary to the concept of living law. Considering this, the urgent application of disruptive marketing by app-based transportation providers is essential to foster innovation without infringing upon the principles and laws of fair competition.